The Role of Digital Marketing in Enhancing Tourism Demand: A Conceptual and Analytical Perspective - Imane , Rezig; Yacine , Guerad; Athmane , Allam (Journal of Ecohumanism, 2025)
Digital transformation has profoundly reshaped the tourism industry by altering how tourists search for information, evaluate destinations, and make travel decisions. In this context, digital marketing has emerged as a strategic instrument for enhancing tourism demand. This paper provides a conceptual and analytical examination of the role of digital marketing in stimulating tourism demand, with particular attention to the behavioral and informational mechanisms through which digital marketing influences tourist decision-making. Drawing on insights from tourism marketing, behavioral economics, and information economics, the study develops an integrated theoretical framework that links digital marketing tools to tourism demand through mediating factors such as destination image, trust, perceived risk reduction, and emotional engagement. The analysis further emphasizes the moderating role of tourism enterprises—especially small and medium-sized enterprises—and institutional support in shaping the effectiveness of digital marketing strategies The study contributes to the tourism literature by synthesizing fragmented research into a coherent analytical perspective and by highlighting digital marketing as a key driver of tourism demand in an increasingly competitive and information-intensive environment. The findings offer valuable implications for policymakers and tourism managers seeking to design effective, data-driven, and sustainable digital marketing strategies.